Pengaruh Media Sosial terhadap Motivasi Anak Melakukan Tindak Kekerasan di Kota Cirebon - Rio Alexandro; Alip Rahman; M. Noupel (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the factors that cause social media to influence children's motivation to commit acts of violence in Cirebon City and the government's efforts to prevent and address it. The study used an empirical legal method with a legislative and sociological approach. Data were obtained through interviews and literature studies, then analyzed qualitatively. The results show that children's motivation to commit acts of violence is influenced by exposure to violent content, imitation processes, the need for social validation, the influence of their social environment, and low digital literacy. Government efforts are carried out through education, digital literacy, legal counseling, school guidance, and cross-sector synergy, but their effectiveness still faces various obstacles in their implementation.